2014
DOI: 10.1002/2014ja020062
|View full text |Cite
|
Sign up to set email alerts
|

Antidipolarization fronts observed by ARTEMIS

Abstract: Near-Earth reconnection on closed plasma sheet field lines is thought to generate plasmoids. A plasmoid is usually described as a plasma sheet expansion into the lobe, encompassed by closed magnetic loops or the helical fields of a flux rope (in this paper we do not distinguish plasmoids from flux ropes; rather we use the term plasmoid generically). Recently, sharp, highly asymmetric north-then-south bipolar variations (with a larger southward portion) in the magnetic field B Z component have been noted in mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 56 publications
(92 reference statements)
5
47
0
Order By: Relevance
“…Considered a boundary between reconnection outflow and the ambient plasma, TDFB is typically accompanied by quick density drop and particle heating, while a CRDD does not correspond to a sharp boundary of plasma populations. The morphological difference is similar to the comparison of antidipolarization and plasmoids presented in Li et al [].…”
Section: Resultssupporting
confidence: 87%
“…Considered a boundary between reconnection outflow and the ambient plasma, TDFB is typically accompanied by quick density drop and particle heating, while a CRDD does not correspond to a sharp boundary of plasma populations. The morphological difference is similar to the comparison of antidipolarization and plasmoids presented in Li et al [].…”
Section: Resultssupporting
confidence: 87%
“…These characteristics are similar to those of DFBs observed at R > 15 R E by THEMIS (Runov et al, ). It is notable that the positive B z excursion preceding the fronts, which is clearly visible in the ADF statistics (Li et al, ) and in the example shown in Figure , is not evident in the superposed B z in Figure b. This is likely because of our choice of t 0 : the time delay between the B z >0 interval and t 0 varies from event to event and does not leave a signature in the superposed epoch plot.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast to the earthward DFB‐associated flows in the near‐Earth plasma sheet (see Figure 2 in Runov et al, ), the tailward flows on average begin more than 100 s ahead of the B z front and continue more than 300 s behind the front. It was shown that the tailward plasma flow speed starts to increase, on average, 2 to 3 min prior to the ADF detection time (Li, Liu, et al, , Zhou et al, ). This precursor flow may be explained by a compression of ambient plasma ahead of the ADF or by reflection of ambient ions from the ADF (Zhou et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations